1999
DOI: 10.1044/jslhr.4201.195
|View full text |Cite
|
Sign up to set email alerts
|

Naming Errors of Children With Specific Language Impairment

Abstract: This paper explores why children with SLI are less accurate than peers in naming pictures. Subjects included 66 children with SLI (aged 4:3 to 9:7) with 2 subgroups, one with expressive-only language deficits (SLIexp) and one with receptive and expressive language deficits (SLImix), and 66 children with no language impairment (NLI). Children with SLI made more errors than children with NLI, and proportionally more of their errors were names of objects associated with the pictured object (e.g., shoe/foot) and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
94
1
7

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(109 citation statements)
references
References 19 publications
7
94
1
7
Order By: Relevance
“…The categorization of error types was based on the categorization of Lahey and Edwards (1999). To circumvent extremely low frequencies for some error types, the different categories were collapsed into the categories of semantic errors, phonological errors, "nonrelated" errors, and a category consisting of omissions and circumlocutions.…”
Section: Stimulimentioning
confidence: 99%
See 3 more Smart Citations
“…The categorization of error types was based on the categorization of Lahey and Edwards (1999). To circumvent extremely low frequencies for some error types, the different categories were collapsed into the categories of semantic errors, phonological errors, "nonrelated" errors, and a category consisting of omissions and circumlocutions.…”
Section: Stimulimentioning
confidence: 99%
“…As such, the distribution of errors could provide clinicians with an indication of the type of language deficit. For example, Lahey and Edwards (1999) found that 6-year-old children with receptive language problems were more likely to make semantic errors, whereas their peers with expressive language problems showed a higher likelihood of phonological errors. Studies on picture naming skills in children with SLI found a lower naming accuracy compared with TD children (e.g., Lahey & Edwards, 1999;.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In this way, when the novel words were encountered, a child needed to create a semantic representation of the referent, a lexical representation of the whole word form, and an association between the two. We hypothesized that analysis of children's error patterns may provide insights into which type of representation, lexical or semantic, may be most affected by phonotactic probability (cf., Lahey & Edwards, 1999;McGregor, 1997). Two factors were considered: (1) error type; (2) Preschool children were recruited from the local community through posted announcements and newspaper advertisements.…”
mentioning
confidence: 99%